Application of the computational modeling in the resin transfer molding (RTM) process: a case study of a marine propeller - Porto, Joseane da Silva (2012)
This work presents one example of how the computational modeling can help in the Resin Transfer Molding (RTM) process when it is applied to the production of parts with complex geometry, such as the marine propellers. This manufacture process of composite material parts consists in the injection of a polymeric resin into a closed mold where a fibrous reinforcement is previously placed. The numerical simulation of the RTM process can be considered as the resin flow through a porous media. This computational model was developed in the FLUENT package, which is based on the Finite Volume Method (FVM), and was applied to study a propeller for naval propulsion. As the propeller has a complex format, the use of computational approach as a preliminar step in the manufacturing process is very important for the correct definition of the inlet and outlet nozzles. So, it is possible to design an efficient mold, avoinding extras costs related with the mold redesign, the resin waste and the increase of injection time. The results showed that an inadequate positioning of the mold outlet nozzles causes an increase about 10% and 2% in the production time and in the resin amount, respectively, for obtaining the marine propeller by RTM process.